The impact of climate change mitigation on water demand for energy and food: An integrated analysis based on the Shared Socioeconomic Pathways. Issue 64 (October 2016) - Mouratiadou, Ioanna; Biewald, Anne; Pehl, Michaja; Bonsch, Markus; Baumstark, Lavinia; Klein, David; Popp, Alexander; Luderer, Gunnar; Kriegler, Elmar
Highlights: We use an integrated modelling framework of the water-energy-land-climate systems. We assess the effects of socioeconomics, mitigation & water policy on water demand. The impacts of climate change mitigation on water demand are highly uncertain. The choice of cooling systems is a major determinant of electricity water demand. Dedicated policies on irrigation of bioenergy and electricity water use are needed. Abstract: Climate change mitigation, in the context of growing population and ever increasing economic activity, will require a transformation of energy and agricultural systems, posing significant challenges to global water resources. We use an integrated modelling framework of the water-energy-land-climate systems to assess how changes in electricity and land use, induced by climate change mitigation, impact on water demand under alternative socioeconomic (Shared Socioeconomic Pathways) and water policy assumptions (irrigation of bioenergy crops, cooling technologies for electricity generation). The impacts of climate change mitigation on cumulated global water demand across the century are highly uncertain, and depending on socioeconomic and water policy conditions, they range from a reduction of 15, 000 km 3 to an increase of more than 160, 000 km 3 . The impact of irrigation of bioenergy crops is the most prominent factor, leading to significantly higher water requirements under climate change mitigation if bioenergy crops are irrigated. Differences in socioeconomic drivers and fossil fuel availability result in significant differences in electricity and bioenergy demands, in the associated electricity and primary energy mixes, and consequently in water demand. Economic affluence and abundance of fossil fuels aggravate pressures on water resources due to higher energy demand and greater deployment of water intensive technologies such as bioenergy and nuclear power. The evolution of future cooling systems is also identified as an important determinant of electricity water demand. Climate policy can result in a reduction of water demand if combined with policies on irrigation of bioenergy, and the deployment of non-water-intensive electricity sources and cooling types.